The study fluid analysis of a new blowdown pump sealing line - Raihan Muhammad (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2023)
The sealing system is used on the pump as a sealing medium between a stationary object (the pump casing) and a rotating object (shaft), maintains the shaft temperature, and keeps the fluid not in or out of the system. The blowdown pump in Priok Combined Cycle Power Plant (CCPP) used service water as a medium for the sealing system because potential seawater will contaminate the pumped water. In this case, the authors observe a blowdown pump, one of the pumps in the desalination system that pumps the seawater. There is no potential for contaminating fluid systems by sealing water because the fluid contains many salts and is thrown directly into the ocean. This project is to replace the water sealing using seawater as a sealing system on the blowdown pump will not harm the system because the fluid system is carried out. This research can reduce the use of water service by as much as 1142 liters per day for 2 desalination plants because the discharge water used sealing each desalination unit is 23,79 liters / hour / desalination.